A case of surgically treated non-metastatic SMARCA4-deficient undifferentiated thoracic tumor: a case report and literature review - Yin, Cong; Liu, Zheng-jia; He, Chao; Yu, Hai-xiang (Frontiers in Oncology, 2024)
SMARCA4-deficient undifferentiated thoracic tumor (SMARCA4-UT) is a rare malignant tumor characterized by inactivation of the SMARCA4 gene and the presence of undifferentiated or rhabdoid morphology in the tissue. This tumor is highly invasive, typically diagnosed at advanced stages III or IV, and commonly involves thoracic structures, such as the mediastinum and chest wall. Reported cases are limited and treatment guidelines have not yet been established. Here, we present a rare case of surgically treated non-metastatic SMARCA4-UT. The patient presented with blood-tinged sputum, dyspnea, and a history of heavy smoking, and underwent surgery after preoperative evaluation ruled out contraindications. The tumor was successfully removed along with the relevant lymph nodes; analysis determined it to be stage IIB T3N0M0. No recurrence was detected at two months post-surgery. However, four months after surgery, the tumor recurred and invaded the adjacent ribs. The diagnosis, differential diagnosis, and treatment of SMARCA4-deficient undifferentiated lung tumors is considered. The combination of chemotherapy and immunotherapy has shown efficacy, and other treatments such as anti-angiogenic drugs, histone deacetylase inhibitors (HDACi), enhancer of zeste 2 polycomb repressive complex 2 subunit (EZH2) inhibitors, and oxidative phosphorylation (OXPHOS) inhibitors may also be beneficial in treating SMARCA4-UT.